Kenaf (Hibiscus cannabinus L.) under varied thermo-mechanical pulping and its influence on medium density fibreboard performance - Alias, Aisyah Humaira (2013)
The medium density fibreboard (MDF) industry is facing shortage of wood resource and tends to utilize non-wood as main raw material. Kenaf (Hibiscus cannabinus L.) has been recognized as one of the potential lignocellulosic materials to replace wood in this industry. Kenaf consists of two major parts :bast and core, and there were identified have greatly different properties in term of anatomy, physical and chemical content. Due to these differences, both parts are refined separately and the behaviour of these fibres were observed. In this study, MDF were manufactured from bast and core fibres of kenaf using various refining conditions from thermo-mechanical pulping (TMP). The fibres were refined at three different digestion pressures of 3, 5 and 7 bar and at temperatures of 140, 160 and 180°C, respectively. Two heating refining times of 3 and 5 minutes were used. The fibre morphology, surface, buffering capacity and size distribution were evaluated. The resulting fibres were used to manufacture MDF panesl at a target density of 700 kg/m3 and using 12% of urea-formaldehyde as binder. The panels were than evaluated according to Malaysian Standard 1787. Generally, the TMP condition affects the fibre properties of bast and core fibres. Bast produced longer and wider fibres with high aspect ratio compared to core. At highest pressure (7 bar), the waxy surfaces of bast fibres melted while core contained more fines. The pH of core was more acidic compared to bast after refining, where the core was more sensitive to acid and bast was more sensitive to alkaline. Among the three refining conditions, the fibres from bast refined with 5 bar pressure for 5 minutes resulted in better mechanical and physical properties of the panels. The panel recorded highest modulus of rupture (MOR) of 22.9 MPa,modulus of elasticity (MOE) of 2113 MPa and internal bonding (IB) of 0.17 MPa. The panel properties were affected by the fibre length and the presence of wax on fibre surfaces. For core panel, fibres refined at 7 bar pressure for 5 minutes resulted in better mechanical and physical properties with the value of 30.3, 3619 and 0.66 MPa for MOR, MOE and IB, respectively. The bending strength of the panels were availability of more fines produced at higher pressure. The bonding was affected by the properties of the core that was sensitive towards acid, resulted in the sufficient curing between the fibres and adhesive during pressing, thus was producing panels with good bonding properties. The dimensional stability of core panels were more stable compared to bast panel as indicated by the low values in thickness swelling and water absorption. The overall results indicated that bast and core fibre can be used as raw material for MDF manufacture, with right selection of TMP conditions. Panel from core fibre produced better panel properties than bast panel. Thus, core fibre is suitable to be used in the fibreboard productions.